Strategi dan Konsep Teoritis dalam Pembiayaan Pendidikan di Indonesia - Fihana, Mega Yesi Okta (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research seeks to fill this gap by exploring educational funding theory and applying it concretely in the Indonesian context. Thus, it is hoped that this research can provide new insights and significantly contribute to designing more effective and inclusive policies to improve the Indonesian education system.Methods – This research uses a descriptive research type method to better understand education financing from various theoretical and practical perspectives.Findings – The research results show that financing education is very important because education can have significant costs, especially at the higher education level. Indonesia has taken steps to improve education financing and increase the accessibility and quality of education, the application of innovation in education financing in Indonesia has the potential to increase educational resources and the quality of education and ensure that every individual has an equal opportunity to get a quality education, but it is necessary considering Indonesia's social, economic, and cultural context as well as efforts to ensure long-term sustainability.Research Implications – The phenomenon of increasing education costs is a concern and requires a balance between adequate funding, efficient allocation, and transparent management so that the right to education can be enjoyed without financial obstacles by all citizens. studies may not consider local factors that can influence the effectiveness of financing models, such as geographic conditions and cultural diversity in various regions of Indonesia. Further research with a contextual approach can provide more comprehensive insight into education financing problems at the local level.